The effects of a single memantine treatment on behavioral alterations associated with binge alcohol exposure in neonatal rats - Idrus, Nirelia M. (2011)
BACKGROUND: The third trimester in human fetal development represents a critical time of brain maturation referred to as the “brain growth spurt”. This period occurs in rats postnatally, and exposure to ethanol during this time can increase the risk of impairments on a variety of cognitive and motor tasks. It has been proposed that one potential mechanism for the teratogenic effects of ethanol is NMDA receptor-mediated excitotoxicity during periods of ethanol withdrawal. In neonatal rats, antagonism of NMDA receptors during ethanol withdrawal, with drugs such as MK-801 and eliprodil, has been shown to mitigate some of the behavioral deficits induced by developmental ethanol exposure. The current study examined whether memantine, an NMDA receptor antagonist and a drug used clinically in Alzheimer’s patients, would attenuate impairments associated with binge ethanol exposure in neonatal rats. METHODS: On postnatal day 6, rats were exposed to 6 g/kg ethanol via intubation with controls receiving an isocaloric maltose dextrin solution. Twenty-one hours following the ethanol binge, rats received intraperitoneal injections of memantine at 0, 10, 15, or 20 mg/kg. Ethanol’s teratogenic effects were assessed using multiple behavioral tasks: open field activity, parallel bars and spatial discrimination reversal learning. RESULTS: Ethanol-treated rats were overactive in the open field and were impaired on both reversal learning and motor performance. Administration of 15 or 20 mg/kg memantine during withdrawal significantly attenuated ethanol’s adverse effects on motor coordination, but did not significantly alter activity levels or improve the spatial learning deficits associated with neonatal alcohol exposure. CONCLUSION: These results indicate that a single memantine administration during ethanol withdrawal can mitigate motor impairments but not spatial learning impairments or overactivity observed following a binge ethanol exposure during development in the rat.